The Current State and Priorities of Foreign Trade Cooperation of the Kingdom of Morocco with the Post-Soviet Countries - S. GACIM (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
More than a century has passed since the collapse of the soviet area, but its transformation continues, creating new opportunities for the development of international trade cooperation. The potential of this transformation is mostly used by developed countries to form a more effective foreign trade system, but is not sufficiently used by most developing countries, in particular, the Kingdom of Morocco. At the same time, the issue of diversification of foreign trade remains an urgent task for the country for a long time. The study aims to identify special features and to justify the priorities of foreign trade cooperation of the Kingdom of Morocco with the post-soviet countries.The article investigates the features of foreign trade cooperation of the Kingdom of Morocco with the post-soviet countries except for the Baltic States. The export and import matrixes of the Kingdom of Morocco with these countries has been constructed and the key locations of Moroccan foreign trade has been determined in the following regions: Eastern European countries (Ukraine, Belarus and Moldova); Central Asian countries (Kazakhstan, Kyrgyzstan, Tajikistan, Uzbekistan, Turkmenistan); the countries of the South Caucasus (Georgia, Armenia, Azerbaijan) and Russia as a territory with unique geographical and economic features. It has been established that the intensity and stability of foreign trade operations of the Kingdom of Morocco is significantly different in the countries and regions of the post-soviet area. The key features of the foreign trade of the Kingdom of Morocco with the post-soviet countries has been defined: the negative balance of foreign trade, the high importance of critical commodities in the import of the country and a significant proportion of technological goods in the country's exports.It is substantiated that the priority of development of Moroccan foreign trade cooperation with the post-soviet countries should be to increase exports, primarily electrical products and vehicles. It is indicated the possibility for exports of used cars, cheap clothes, as well as fish and canned fish in regions with low purchasing power. Another priority in the post-soviet area has been proposed, that is to identify alternative markets to diversify the supply of goods traditionally imported by the Kingdom of Morocco from other countries of the world economy, in particular cotton.